2018
DOI: 10.3390/ijms19113408
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Combination of Ion Channel Inhibitors in Female Rats Following Repeated Mild Traumatic Brain Injury

Abstract: Following mild traumatic brain injury (mTBI), the ionic homeostasis of the central nervous system (CNS) becomes imbalanced. Excess Ca2+ influx into cells triggers molecular cascades, which result in detrimental effects. The authors assessed the effects of a combination of ion channel inhibitors (ICI) following repeated mTBI (rmTBI). Adult female rats were subjected to two rmTBI weight-drop injuries 24 h apart, sham procedures (sham), or no procedures (normal). Lomerizine, which inhibits voltage-gated calcium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…In our current study, we present data supporting the concept that uremia stimulates adipocyte production of inflammatory cytokines and promotes lipolysis. This finding is consistent with prior studies that reported increased IL-6 and TNF-α expression in 3T3-L1 adipocytes exposed to uremic toxins such as indoxyl sulfate and p-cresyl sulfate 28 , 29 . Furthermore, we have also demonstrated that macrophages exposed to uremia drive adipocytes to produce inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…In our current study, we present data supporting the concept that uremia stimulates adipocyte production of inflammatory cytokines and promotes lipolysis. This finding is consistent with prior studies that reported increased IL-6 and TNF-α expression in 3T3-L1 adipocytes exposed to uremic toxins such as indoxyl sulfate and p-cresyl sulfate 28 , 29 . Furthermore, we have also demonstrated that macrophages exposed to uremia drive adipocytes to produce inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…In support of this mechanism, animal studies have demonstrated a loss of diffuse noxious inhibitory controls (DNIC) after mTBI, while human studies have demonstrated a loss of conditioned pain modulation, findings reflective of a reduction in pain inhibition (30)(31)(32). As reviewed more comprehensively in an article by H Ashina and colleagues, cellular injury due to mTBI results in loss of normal ionic homeostasis, energy depletion, oxidative stress, and axonal damage, processes that could contribute to the development and persistence of PTH (29,33,34). TBI, including mTBI, might trigger cortical spreading depression (CSD) at the time of injury and be associated with the extent of brain tissue injury and functional outcomes (35).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Administration of BBG reduced cord damage and improved motor recovery, associated with reduced inflammatory and glial activation, and infiltration (Peng et al, 2009 ). The combination of systemically administered Lom, YM872, and BBG have shown good effects in a rodent model of repeated mild traumatic brain injury and comparable to local delivery at improving outcomes following partial optic nerve transection (Mao et al, 2018 ; Toomey et al, 2019 ). Therefore, future studies should assess the effects of systemic delivery of blood-brain-barrier permeable Lom and YM872 (Nishiyama et al, 1999 ) with BBG, following SCI.…”
Section: Discussionmentioning
confidence: 99%